Efeito da terapia fotônica no tratamento de lesões traumáticas de tecidos moles: ensaio clínico controlado randomizado duplo-cego - Jaña Neto, Frederico Carlos (2022)
Soft tissue injuries are directly related to the energy of trauma and their repair is the main factor for bone healing and recovery of the affected limb function. Photonic therapies (TF) are indicated as adjuvant treatments in decontamination and acceleration of wound heal-ing, however, there is still a lack of evidence regarding their effect on soft tissue injuries of traumatic origin. The main objective of this study was to evaluate the efficacy and safety of ST using LEDs in the healing process of soft tissue injuries associated with tibial fractures. We included 27 adult individuals, aged between 18 and 72 years, hospitalized with a tibial frac-ture who were awaiting resolution of the soft tissue injuries to undergo definitive surgery. Participants were randomized into two groups: TF (device with 144 LED emitting diodes at wavelengths of 420, 660 and 850nm, 3J per point for 10 minutes) and simulated TF (sham) (device with identical external characteristics but no of light). The primary outcome measure was the assessment of the wound healing process as measured by the variation of the BATES-JENSEN (BJ) scale. Secondary outcomes were: time to release for definitive surgery, pain intensity, consumption of analgesic drugs, area of injury and presence of adverse events. An economic analysis of the treatments was also performed. Assessments were performed before the start of the intervention and daily until the participant was considered to have resolved the wound. Data were statistically analyzed considering a significance level of 5%. The daily mean in the BJ classification showed a significant difference in the direct comparison between the groups (Control 34.26 ±0.90 versus TF 32.10 ±1.23 (p=0.03)). There was a significant dif-ference in the change in the pain score from the 5th to the last day (2.1 ±1.2 versus 0.8 ±1.7 (p = 0.02)) and in the mean rate of daily change in the pain scale to favor of the TF group (0.58 ±0.38 versus 0.28 ±0.37). The average time for wound resolution of the participants was 13.1 days (±11.5) in the intervention group (TF) and 23.1 days (±21.3) in the control group, but this difference cannot be considered statistically. significant between groups (p = 0.76). There was a statistically significant difference (p=0.02) in the occurrence of infection in the path of the external fixator pins, four times more frequent in the Control group (n=8/14) than in the TF group (n=2/13). By subdividing the population into subgroups considering the severity of the injury, among the patients with less severity, it was possible to observe statistically signifi-cant differences between the groups in the daily mean of the BJ scale (Control 34.78 versus TF 27.46 (p=0.0081)). The time in which less severe patients undergoing TF reached the pa-rameters of release for surgery was significantly shorter than the control group, with a differ-ence of approximately 7 days (mean intervention 7.0 versus control 14.6 days; p = 0, 03). In patients who had more severe injuries, there was no difference between the groups in the time of evolution (mean TF 26.25 versus control 44.25 days p=0.28). In the economic analysis of the data from all patients, in the daily average item on the BJ scale, the TF treatment was dominant because it presented greater effectiveness and lower cost, therefore, it can be con-sidered an alternative for insertion in health services. As implications for practice, the use of TF is safe and seems to have better efficacy in less severe and more superficial injuries, reduc-ing wound resolution time, and consequently, the time for definitive surgery, the hospitaliza-tion period and the treatment costs.